2007
DOI: 10.1161/circresaha.107.149435
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Hemoglobin Scavenger Receptor in Individuals With Diabetes and the Hp 2-2 Genotype

Abstract: Abstract-In individuals with diabetes mellitus (DM), the haptoglobin (Hp) genotype is a major determinant of susceptibility to myocardial infarction. We have proposed that this is because of DM and Hp genotype-dependent differences in the response to intraplaque hemorrhage. The macrophage hemoglobin scavenging receptor CD163 plays an essential role in the clearance of hemoglobin released from lysed red blood cells after intraplaque hemorrhage. We sought to test the hypothesis that expression of CD163 is DM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 35 publications
8
100
3
1
Order By: Relevance
“…Therefore, oxidative conditions, such as diabetes mellitus, can cause elevated serum sCD163 levels (9 Moreover, sCD163 is found to be increased during wound healing, giving a possible role of CD163 in the pathogenesis of fibrotic diseases and the remodeling of connective tissues (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, oxidative conditions, such as diabetes mellitus, can cause elevated serum sCD163 levels (9 Moreover, sCD163 is found to be increased during wound healing, giving a possible role of CD163 in the pathogenesis of fibrotic diseases and the remodeling of connective tissues (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that TACE is also responsible for the shedding of macrophagespecific soluble CD163 (sCD163) [9]. Plasma sCD163 is regarded as a longer duration circulating marker of TNF-α, and concentrations of sCD163 are increased in obese [10,11] and type 2 diabetic patients [12], consistent with macrophage accumulation in the adipose tissue. Zanni et al, in a study which was published while this manuscript was under review, reported a strong association between sCD163 and insulin resistance in obese individuals and normal-weight controls [11].…”
Section: Introductionmentioning
confidence: 99%
“…An approximately 130 kDa soluble form of human CD163 is released from the cell surface by proteolysis after oxidative stress or inflammatory stimuli. Thus, elevated level of circulating soluble CD163 (sCD163) has been reported in diabetes mellitus, which is one of oxidative conditions [12]. However, there have been no studies examining the involvement of sCD163 in SSc patients to our knowledge.…”
Section: Introductionmentioning
confidence: 99%